Transcriptomic Insight in the Control of Legume Root Secondary Infection by the Sinorhizobium meliloti Transcriptional Regulator Clr - Zou, Lan; Gastebois, Amandine; Mathieu-Demazière, Céline; Sorroche, Fernando; Masson-Boivin, Catherine; Batut, Jacques; Garnerone, Anne-Marie (Frontiers in Microbiology, 2017)
The cAMP-dependent transcriptional regulator Clr of Sinorhizobium meliloti regulates the overall number of infection events on Medicago roots by a so-far unknown mechanism requiring smc02178, a Clr-target gene of unknown function. In order to shed light on the mode of action of Clr on infection and potentially reveal additional biological functions for Clr, we inventoried genomic Clr target genes by transcriptome profiling. We have found that Clr positively controls the synthesis of cAMP-dependent succinoglycan as well as the expression of genes involved in the synthesis of a so-far unknown polysaccharide compound. In addition, Clr activated expression of 24 genes of unknown function in addition to smc02178. Genes negatively-controlled by Clr were mainly involved in swimming motility and chemotaxis. Functional characterization of two novel Clr-activated genes of unknown function, smb20495 and smc02177, showed that their expression was activated by the same plant signal as smc02178 ex planta. In planta however, symbiotic expression of smc02177 proved independent of clr. Both smc02177 and smb20495 genes were strictly required for the control of secondary infection on Medicago sativa. None of the three smc02177, smc02178 and smb20495 genes were needed for plant signal perception. Altogether this work provides a refined view of the cAMP-dependent Clr regulon of S. meliloti. We specifically discuss the possible roles of smc02177, smc02178, smb20495 genes and other Clr-controlled genes in the control of secondary infection of Medicago roots.